Characteristics and Social Principles of Psychological Counseling in Schools - Karajonova Bakhtigul Tajiyevna (International Journal on Integrated Education, 2022)
The article describes the theoretical foundations of psychological counseling within the framework of psychological services in schools, the features and social principles of psychological counseling in schools, the level of social protection of a person, and a number of important functions for society and the individual.